Mechanics Design of Conical Spiral Structure for Flexible Coilable Antenna Array - Hairui Wang; Yao Zhang; Siyu Chen; Yinji Ma; Heling Wang; Ying Chen; Xue Feng (International Journal of Aerospace Engineering)
Limited by the effective launch capacity of a rocket, the deployable antenna is very important in the design of spaceborne antenna array. Compared to traditional deployable antenna, flexible coilable antenna array has higher surface precision and better vibration control and therefore is more suitable for high frequency communication. In order to minimize the weight of satellite and reduce cost of its launch, a design guideline to the geometry parameters of flexible coilable antenna array is crucial. Existing models cannot be directly applied to interaction and large deformation between coilable membrane and conical spiral antenna in the flexible coilable antenna array. Hence, the geometry parameters of the conical spiral structure and the thickness of the coilable membrane in the flexible coilable antenna array have not been optimized yet. In this paper, the interaction between the coilable membrane and the concial spiral antenna is analyzed in the antenna array. A concise formula is derived to predict the critical force that flattens the conical spiral antenna by a coiling scroll. Combined with a theoretical model to predict the deformation of the membrane, the model provides an important theoretical support for the lightweight design and mechanical design of flexible coilable antenna array, such as the thickness of the coilable membrane. The proposed design is validated by experiments. The above findings have potential applications in the effective reduction of antenna array weight and satellite launch costs.